2013
DOI: 10.1021/om400246a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of the Pd/TOMPP-Catalyzed Telomerization of 1,3-Butadiene: Influence of Aromatic Solvents on Bis-Phosphine Complex Formation and Regioselectivity

Abstract: A study of the influence of reaction conditions on the Pd/TOMPP-catalyzed (TOMPP = tris(2-methoxyphenyl)phosphine) telomerization of 1,3-butadiene with phenols revealed that the composition of the reaction medium strongly influences the regioselectivity of the telomer products. Mechanistic studies show this effect to be related to the stability of the key catalytic intermediate cis-[Pd((1–3η)-octa-2,7-dien-1-yl)(TOMPP)2]+ (E), which mainly depends on the solvent composition. The crotyl analogue cis-[Pd((1–3η)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The reaction of the intermediate with methanol yielded the respective telomers and it could be demonstrated that the electronic (ν CO ) as well as the steric (θ) properties of the phosphorus ligand greatly influence the reactivity. It could later be shown that the η 3 ‐allyl species (similar to complex D in Scheme , but with an additional P‐ligand instead of the coordinated double bond) is stabilized by aromatic solvents, thus leading to the conclusion that this is the key intermediate for aromatic substrates such as phenols . The non‐chelated species, which can also be favored by a high ligand excess, leads to lower selectivities to the linear product .…”
Section: Catalystsmentioning
confidence: 99%
“…The reaction of the intermediate with methanol yielded the respective telomers and it could be demonstrated that the electronic (ν CO ) as well as the steric (θ) properties of the phosphorus ligand greatly influence the reactivity. It could later be shown that the η 3 ‐allyl species (similar to complex D in Scheme , but with an additional P‐ligand instead of the coordinated double bond) is stabilized by aromatic solvents, thus leading to the conclusion that this is the key intermediate for aromatic substrates such as phenols . The non‐chelated species, which can also be favored by a high ligand excess, leads to lower selectivities to the linear product .…”
Section: Catalystsmentioning
confidence: 99%
“…Further work is underway to fully explore the role of L6 in promoting catalysis, including the potential for supporting cationic Pd II intermediates. [66][67][68] In summary, we have demonstrated that Pd catalysis is effective for the cross-coupling of alkenyl carboxylates. This observation, contrary to the often observed and generally accepted reactivity patterns for Pd-catalyzed cross-coupling, opens the door to discovery of new methods complementary to those involving other transition metals.…”
Section: Methodsmentioning
confidence: 81%
“…While the poor reactivity of Pd 2 dba 3 / L6 relative to both Pd(OAc) 2 / L6 and Pd(Ph)(OAc)( L6 ) is not definitive, the balance of current evidence supports a Pd II ‐mediated mechanism when using L6 rather than one involving Pd 0/II . Further work is underway to fully explore the role of L6 in promoting catalysis, including the potential for supporting cationic Pd II intermediates …”
Section: Methodsmentioning
confidence: 99%